Honduras : Public Expenditure Review, Volume 1. Executive Summary and Main Report - World Bank (Washington, DC, 2012)
Macroeconomic developments in Honduras over the last four years have been generally favorable, largely reflecting a benign external environment. Honduras' medium-term macroeconomic outlook, however, is clouded by several significant fiscal challenges. These challenges include: (a) rising operating losses of the public enterprises; (b) rising public wages; and (c) popular pressures to increase subsidies in transport, fuel, and electricity, as well as to freeze gasoline and energy prices, in the wake of international oil price hikes. To satisfy the rapidly rising demand for education in Honduras, the educational wage bill will have to rise by approximately 41 percent in real terms over the next 10 years. Even without any further adjustments in 2010, due to the agreement reached with the teachers union in August 2006 (PASCE) salary increases are coupled with projected enrollment demand the educational wage bill stands to increase by 141 percent over the next 10 years.